2018
DOI: 10.1039/c8en00071a
|View full text |Cite
|
Sign up to set email alerts
|

Multi-omics approaches confirm metal ions mediate the main toxicological pathways of metal-bearing nanoparticles in lung epithelial A549 cells

Abstract: Our analyses confirm that the dissolution of metal ions mediates the main toxicological pathways of silver and zinc oxide nanoparticles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 57 publications
0
25
0
Order By: Relevance
“…In our previous report, the toxicity of VO 2 to A549 cells had been systematically studied in both short‐term and long‐term exposures, and it was found that the cytotoxicity of VO 2 was mainly attributed to the dissolved species of VO 2 in the culture (Xi et al, ), similar to some other metal oxide NPs with low chemical stability (Dekkers et al, ; Wang et al, ; Yang et al, ). Measurement of the dissolved vanadium species from N‐VO 2 and T‐VO 2 in culture medium showed that the TiO 2 ‐coating could substantially reduce the dissolution of VO 2 (Figure S2).…”
Section: Discussionmentioning
confidence: 99%
“…In our previous report, the toxicity of VO 2 to A549 cells had been systematically studied in both short‐term and long‐term exposures, and it was found that the cytotoxicity of VO 2 was mainly attributed to the dissolved species of VO 2 in the culture (Xi et al, ), similar to some other metal oxide NPs with low chemical stability (Dekkers et al, ; Wang et al, ; Yang et al, ). Measurement of the dissolved vanadium species from N‐VO 2 and T‐VO 2 in culture medium showed that the TiO 2 ‐coating could substantially reduce the dissolution of VO 2 (Figure S2).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, in a ROS-independent manner, AgNPs and the released Ag + ions may interact with the thiol groups of proteins, resulting in protein misfolding and eventually cell death (Riaz Ahmed et al 2017). Metal ions have also been confirmed to mediate the toxicological pathways of metal-bearing NPs in a multiomics study that involved direct infusion mass spectrometry lipidomics, polar metabolomics, and RNA-sequencing transcriptomics (Dekkers et al 2018). In this study, the majority of the molecular responses of human lung epithelial A549 cells to silver (Ag) and zinc oxide (ZnO) NPs-such as metallothionein induction, antioxidant depletion, repressed DNA repair, and apoptosis 15 induction-are similar to their responses to Ag + and Zn 2+ ions, respectively, confirming that the modes of action of these NPs are largely mediated by the corresponding dissolved metal ions.…”
Section: Discussionmentioning
confidence: 99%
“…Metabolites can be discovered through NMR-based metabolomics by detecting characteristic spectral patterns, for example, healthy vs diseased. Principle component analysis (PCA; Figure 7D,F,H,I) and particle least squares discriminant analysis (PLS-DA; Figure 7E,G) subjected to 1D 1 H-NMR spectra of extracts from cancer cells which differentiate the clear separation between control and AgNPs [114]. A PCA represents basic discrimination.…”
Section: Pattern Recognition Of Cancer Cellsmentioning
confidence: 99%
“…The validity of the model was assessed according to cross validation results. Additionally, corresponding loading delivered several metabolic regulations by AgNPs [96,114]. The PLS-DA score plots produced by pairwise comparisons (control and AgNPs).…”
Section: Pattern Recognition Of Cancer Cellsmentioning
confidence: 99%
See 1 more Smart Citation